PERENCANAAN BANGUNAN PENGENDALI SEDIMEN DAERAH ALIRAN SUNGAI KREO KOTA SEMARANG - Wahyu Dwi Wijayanto; Nurrahmat Nurrahmat; Abdul Kadir; Priyo Nugroho Parmantoro (Jurnal Karya Teknik Sipil, 2014)
Kreo River is the part of Garang River which located in Semarang City and the area of this river is 61,059 km2. Kreo River is one of sedimentation contributor for Jatibarang Dam,  an estimated 387,33 Ton/Ha/Years sedimentation which enter in Jatibarang Dam are come from this river. One of the solution for the sedimentation and erosion problem in river is by developing building controller sedimentation or similar called check dam. From the calculation, check dam planned to have physical like as follows : the peak elevation of spillway  main dam in the elevation + 187,419 m with highly effective is  4 m and deepness of foundation is  2 m, wide of spillway main dam  obtained 45 m, with Q plan return period 100 years  to 216,475 m3/s, high of wings main dam  is 3 m at elevation  + 190,419 m with highly of  surveillance is 0,8 m, main dam construction use rubble stone masonry, elevation of peak spillway sub at + 185,419 m with highly obtained 2 m and deepness foundation until 2 m, sub dam construction use rubble stone masonry, the elevation of protection floor at +183,419 m with thickness until 1 m, the construction use rubble stone masonry.